Moderate deficit irrigation improves agronomic performance of quinoa (Chenopodium quinoa Willd.) compared to full irrigation in the central highlands of Peru - Gavino, Esthefany; Ccopi, Dennis; Requena-Rojas, Edilson; Contreras, Jose; Solórzano-Acosta, Richard; Betega, S. D.; Yaranga, Raúl M.; Pizarro, Samuel (Edelweiss Applied Science and Technology, 2026)
This study evaluated the agronomic performance and water productivity of quinoa (Chenopodium quinoa Willd. cv. INIA 433) under three irrigation regimes in the central highlands of Peru: optimal irrigation (Ks = 1.00), moderate deficit (Ks = 0.66), and severe deficit (Ks = 0.49). The experiment combined constant water table lysimeters and field plots, integrating crop coefficient estimation, water balance analysis, and multispectral monitoring (NDVI, NDRE, SRWI) using UAV imagery and ground spectroradiometry. Moderate water stress (Ks = 0.66) significantly improved reproductive performance, producing approximately 8,000 grains per plant compared with ~3,900 grains per plant under optimal irrigation. Grain protein content increased from 4.8% to 6.0%, while evapotranspiration decreased by 37% (from 374.5 to 234.4 mm), markedly improving water use efficiency. In contrast, optimal irrigation promoted maximum vegetative growth (plant height ~110 cm; NDVI 0.7–0.8) but lower reproductive output, whereas severe stress (Ks = 0.49) reduced yield to 4,400 grains per plant and accelerated senescence. Multispectral indices effectively distinguished water stress levels: NDVI reflected canopy vigor, NDRE detected chlorophyll variation, and SRWI captured plant water status. The results demonstrate that regulated deficit irrigation enhances water productivity and grain quality in quinoa. Maintaining Ks values around 0.65–0.70 appears to optimize yield and resource use efficiency in water-limited Andean agroecosystems.